2022
DOI: 10.1590/1516-3180.2021.0145.27072021
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between awareness of cervical cancer and HPV infection and attitudes towards HPV vaccine among women aged 15-49 years: a cross-sectional study

Abstract: INTRODUCTIONAlthough the incidence of cervical cancer has decreased in developed countries over recent decades through effective screening programs, it continues to be an important health problem, especially in developing countries. With 569,847 new cases and 311,365 deaths worldwide in 2018, cervical cancer is expected to be the fourth most common type of cancer and the fourth leading cause of cancer death among women. Out of these deaths, 90% occur in underdeveloped or developing countries. In 2018, 2,356 ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
0
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
2
0
0
3
Order By: Relevance
“…Regarding awareness of the consequences of HPV infection, a considerable proportion of participants (41.6%) recognized that HPV can lead to cervical cancer, and 33.3% recognized that it can cause genital warts. These findings are in line with previous studies that have shown varying levels of awareness regarding the link between HPV and cervical cancer [ 20 , 21 ]. However, it is important to note that a significant proportion of participants were still unaware of these risks, highlighting the need for comprehensive educational campaigns to improve knowledge.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding awareness of the consequences of HPV infection, a considerable proportion of participants (41.6%) recognized that HPV can lead to cervical cancer, and 33.3% recognized that it can cause genital warts. These findings are in line with previous studies that have shown varying levels of awareness regarding the link between HPV and cervical cancer [ 20 , 21 ]. However, it is important to note that a significant proportion of participants were still unaware of these risks, highlighting the need for comprehensive educational campaigns to improve knowledge.…”
Section: Discussionsupporting
confidence: 93%
“…A total of 24.5% were moderate and only 4.4% were categorized as having a good level of knowledge (mean score: 3.56; SD 2.91, out of 11 points). These findings are consistent with the literature wherein most women demonstrated a lack of understanding regarding the basic facts of HPV, infection, screening, and prevention [7][8][9][10][11][12][13]. In Aseer Region, Saudi Arabia, there has been a report that only a small proportion (17.4%) of Saudi females had good knowledge about cervical cancer [14].…”
Section: Discussionsupporting
confidence: 90%
“…A figura 01 abaixo é o fluxograma prisma da seleção dos artigos usados no estudo. A partir dos artigos considerados elegíveis ao presente trabalho, realizou-se estudos nos quais pôde-se identificar que de acordo com Yurtçu et al (2022), o câncer de colo do útero é um tipo de câncer monitorado regularmente por meio de programas de rastreamento em todo o mundo e pode ser tratado rapidamente quando detectado. Os fatores importantes no tratamento dessa doença são o diagnóstico precoce e a conscientização da mulher.…”
Section: Resultsunclassified